Competition between sectors upper middle classes and mobilization capital around the educational offer - van Zanten, Agnès (Profesorado, Revista de Currículum y Formación del Profesorado, 2015)
The main objective of this article is to analyze the socio-cultural and economic relations that occur within the upper middle-class in terms of the provisions and strategies developed by schools in their educational offer. Starting from the categories and their social hierarchy developed in The distinction of Bourdieu, the paper examines the role of the middle-upper classes, the differentiation, and the deployment and accentuation of the cultural and social capital in terms of education provision made by different schools in France. On the one hand, it explores the aspirations, values and assessments of their children, and on the other hand, it analyzes the characteristics and potential that families attribute to the school in that they trust. However, it is evident that the different options contribute in some way to reproducing cultural models.